A Small-Scale shRNA Screen in Primary Mouse Macrophages Identifies a Role for the Rab GTPase Rab1b in Controlling Salmonella Typhi Growth - Solano-Collado, Virtu; Colamarino, Rosa Angela; Calderwood, David A.; Baldassarre, Massimiliano; Spanò, Stefania (Frontiers in Cellular and Infection Microbiology, 2021)
Salmonella Typhi is a human-restricted bacterial pathogen that causes typhoid fever, a life-threatening systemic infection. A fundamental aspect of S. Typhi pathogenesis is its ability to survive in human macrophages but not in macrophages from other animals (i.e. mice). Despite the importance of macrophages in establishing systemic S. Typhi infection, the mechanisms that macrophages use to control the growth of S. Typhi and the role of these mechanisms in the bacterium’s adaptation to the human host are mostly unknown. To facilitate unbiased identification of genes involved in controlling the growth of S. Typhi in macrophages, we report optimized experimental conditions required to perform loss-of function pooled shRNA screens in primary mouse bone-marrow derived macrophages. Following infection with a fluorescent-labeled S. Typhi, infected cells are sorted based on the intensity of fluorescence (i.e. number of intracellular fluorescent bacteria). shRNAs enriched in the fluorescent population are identified by next-generation sequencing. A proof-of-concept screen targeting the mouse Rab GTPases confirmed Rab32 as important to restrict S. Typhi in mouse macrophages. Interestingly and rather unexpectedly, this screen also revealed that Rab1b controls S. Typhi growth in mouse macrophages. This constitutes the first report of a Rab GTPase other than Rab32 involved in S. Typhi host-restriction. The methodology described here should allow genome-wide screening to identify mechanisms controlling the growth of S. Typhi and other intracellular pathogens in primary immune cells.